2020
DOI: 10.1093/hmg/ddaa028
|View full text |Cite
|
Sign up to set email alerts
|

CHCHD2 harboring Parkinson’s disease-linked T61I mutation precipitates inside mitochondria and induces precipitation of wild-type CHCHD2

Abstract: The T61I mutation in coiled-coil-helix-coiled-coil-helix domain containing 2 (CHCHD2), a protein residing in the mitochondrial intermembrane space (IMS), causes an autosomal dominant form of Parkinson’s disease (PD), but the underlying pathogenic mechanisms are not well understood. Here, we compared the subcellular localization and solubility of wild-type (WT) and T61I mutant CHCHD2 in human cells. We found that mitochondrial targeting of both WT and T61I CHCHD2 depended on the four cysteine residues in the C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Further analysis of this pathway has identified that CHCHD2 accumulates in damaged mitochondria and regulates CHCHD10 oligomerisation [60]. CHCHD2 has been shown to play a significant role in the maintenance of mitochondrial cristae [59] as well as stabilising OPA1 to promote mitochondrial fusion [61]. Mutations in CHCHD2 have been demonstrated to induce precipitation of both mutant and wild type (WT) protein in the intermembrane space (IMS) [61] as well as cytochrome C destabilization, impaired respiration, and mitochondrial ROS generation [62].…”
Section: The Effects Of Mutations In Pd Causing Genes On Mitochondrial Function and Mitophagymentioning
confidence: 99%
“…Further analysis of this pathway has identified that CHCHD2 accumulates in damaged mitochondria and regulates CHCHD10 oligomerisation [60]. CHCHD2 has been shown to play a significant role in the maintenance of mitochondrial cristae [59] as well as stabilising OPA1 to promote mitochondrial fusion [61]. Mutations in CHCHD2 have been demonstrated to induce precipitation of both mutant and wild type (WT) protein in the intermembrane space (IMS) [61] as well as cytochrome C destabilization, impaired respiration, and mitochondrial ROS generation [62].…”
Section: The Effects Of Mutations In Pd Causing Genes On Mitochondrial Function and Mitophagymentioning
confidence: 99%
“…Depleted MNRR1 protein levels have been found in an in vivo model for juvenile Niemann Pick type C disease [82] and in vitro model for MELAS (Mitochondrial Encephalomyopathy Lactic Acidosis and Stroke-like episodes) syndrome [32]. Mutations in MNRR1 have been associated with a number of neurodegenerative diseases such as Parkinson's [83][84][85], Alzheimer's [86,87], and Charcot-Marie-Tooth disease type 1A [28]. Of note, MELAS, caused by a mtDNA mutation in the mitochondrial tRNA Leu(UUR) gene (m.3243A > G), has been associated with spontaneous preterm birth [88,89] and increased incidence of preeclampsia and gestational diabetes mellitus [88].…”
Section: Discussionmentioning
confidence: 99%
“…α-Synuclein aggregation was accelerated by CHCHD2 T61I in human cells and in Drosophila. Human cells from T61I patients show accumulated CHCHD2 in the mitochondrial intermembrane space (IMS), resulting in increased ROS and apoptosis ( Cornelissen et al, 2020 ).…”
Section: Park Genes In Mitochondrial Function and Homeostatic Controlmentioning
confidence: 99%